Application of Magnetic Force to Means of Transportation Magnetic Levitation High-Speed Railway - Lamablawa, Florianus; Aritonang, Sovian (DAS Institute, 2022)
A magnet or magazine is an object that has a magnetic field. Magnets can also be interpreted as objects with symptoms and properties affecting certain materials around them. Magnetic force is one part of the electromagnetic force, where the other force becomes the fundamental force of nature caused by the movements of charge. Because magnets only attract particular objects, they can also not work or are not stylized, or there can even be a rejection of some particular objects on the magnet. The new generation of transportation is fast, reliable, and safe. In addition, it is also convenient, environmentally friendly, easy maintenance, and supports mass transportation. Magnetic levitation (maglev) trains are among the best candidates that meet these requirements.